Design LTE Microstrip Antenna Rectangular Patch with Beetle-Shaped Slot - Yusnita Rahayu; Haziq Hazman; Razali Ngah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
In this paper, the microstrip antenna rectangular patch with beetle shaped slot is presented. The characterization results of the proposed antenna obtained by changing the dimensions of the ground plane. CST software is used to design and analyze this proposed antenna. The simulated results of proposed antenna show that the antenna works at the frequency of 2.1 GHz while the return loss of -32.18 dB with the bandwidth reaches 155.19 MHz and the gain of 3.895 dBi.